Archaeologiae una storia al plural : studi in memoria di Sara Santoro - Santoro, Sara,; Antonelli, Sonia, (RES: reports, excavations and studies of the archaeological unit of the University G. D'Annunzio of Chieti-Pescara ;, 2022)
Dedicated to the late Sara Santoro, an archaeologist and multifaceted scholar who worked actively in Italy, France and Albania, this volume is divided into six sections, considering topics that include iconography and philology; Adriatic studies; field research; valorisation and planning in cultural heritage; 'minor' settlements; and more.